(untitled) (Bangladesh Journal of Medical Science, 2019)
Introduction: Asthma is a chronic inflammatory condition that affect physically, emotionally and psychologically. In adolescent, various factors contributed to poor asthma control. This study aims to identify treatment adherence, quality of life, knowledge and attitude in adolescents with asthma. Method: This cross-sectional study randomly selected 14 schools in two districts of a state in North-eastern of Malaysia. Complete information was obtained from 262 adolescents aged 13 to 18 years old, who were diagnosed with bronchial asthma in the last six months or having recurrent wheeze for the past 12 months. The tools used include Asthma control test; Asthma treatment adherence; Knowledge on asthma; Attitude on asthma; Paediatric asthma quality of life questionnaires have undergone various process of translation, face validation and assessment of the reliability and validity to achieve a standardized Malay language version. Results: There were about 30% of the adolescent who have not taking their medicine regularly with 50% non-compliant once symptom control was achieved. 22.5% of the participants felt embarrass when using inhaler in front of their friends. Our study showed a higher adherenceto medication of more than 70% compared to other studies. However, more than 50% of of the participants have minimal understanding on the disease natural history. Approximately 20-30% of them admitted of experiencing overall poor quality of life at the time of the study. Conclusion: Most participants reported having good asthma treatment adherence; but in our study, half of the adolescent have poor knowledge of asthma and negative attitude towards medication which influenced the quality of life. Bangladesh Journal of Medical Science Vol.19(1) 2020 p.73-82